Marginalization of Indigenous People in Development: Antimun Bungkuak in the Heart of Minangkabau, Indonesia - Yazan, Sheiful; Arwemi, Arwemi; Kustati, Martin; Perrodin, David D; Elmizan, Gina Havieza (Journal of Innovation in Educational and Cultural Research, 2025)
Indigenous communities are among the vulnerable groups at risk of being left behind in the development process. To uphold the "leave no one behind" principle of the 2030 Sustainable Development Goals (SDGs), it is crucial to examine public policies affecting indigenous peoples. This article focuses on the indigenous community in Bukittinggi, specifically the Kurai people. The research was conducted using a qualitative approach, combining an analysis of public policy documents with field research on the traditional leaders of Kurai Limo Jorong. The findings reveal that the Kurai Indigenous community in Bukittinggi resembles antimun bungkuak—present yet unrecognized. While they remain de facto founders of the city, with leaders and traditional institutions still in place, their influence has steadily declined. Public policies have progressively marginalized them, excluding their existence from official development plans and decision-making processes.